Estimation of Natural Radioactivity and Radiation Hazards Indices of Some Organic Fertilizers Used in Al-Gable Al-Akhdar, Libya (Al-Mukhtar Journal of Basic Sciences, 2026)
In the present work, an assessment of the following levels of natural radioactivity in 5 samples of organicafertilizers collected from the market in Al Bayda City, Libya. Sodium iodide (NaI) gamma spectroscopy was used. The activityaconcentrations ofaradionuclides in the 238U and 232Th natural decayachain as well as 40K wereadetermined. The average activity concentrations in 226Ra, 238U, 232Th and 40K in the samples studied were found to be (± 62.74, ± 64.42, ±63.63 and ±70.88 Bq Kg-1 (for samples. The results of this study have been compared with the worldarecommended values of (1550, 1500, (7-50) and (100-700)) Bqkg-1, respectively as specified by the [UNSCEAR, 2016]. The results showed that all samples had lower levels of radioactivity than the recommended limits for 226Ra, 238U, 40K for organic fertilizers and the activity concentrations were below the thorium (7-50 Bq kg-1) except fo1,fo4 and fo5 were higher  than the recommended limits. , The a radium equivalent, absorbed dose rate in air, annual effective dose equivalent for indoor and outdoor exposure, excess lifetime cancerarisk, internal and external hazard indicators were calculated. The results ofamost samples were within theaglobal averagearecommended by [ UNSCEAR,2016]. So, it is safe to consume andadoes not pose a threat to the general public.